Spell Sequences, State Proximities, and Distance Metrics. (February 2015) - Elzinga, Cees H.; Studer, Matthias
Because optimal matching (OM) distance is not very sensitive to differences in the order of states, we introduce a subsequence-based distance measure that can be adapted to subsequence length, to subsequence duration, and to soft-matching of states. Using a simulation technique developed by Studer, we investigate the sensitivity, relative to OM, of several variants of this metric to variations in order, timing, and duration of states. The results show that the behavior of the metric is as intended. Furthermore, we use family formation data from the Swiss Household Panel to compare a few variants of the new metric to OM. The new metrics have been implemented in the freely available TraMineR-package.